Single-unit activities during epileptic discharges in the human hippocampal formation - Alvarado-Rojas, Catalina; Lehongre, Katia; Bagdasaryan, Juliane; Bragin, Anatol; Staba, Richard; Engel, Jerome; Navarro, Vincent; LE VAN QUYEN, Michel (Frontiers in Computational Neuroscience, 2013)
Between seizures the brain of patients with epilepsy generates pathological patterns of synchronous activity, designated as interictal epileptiform discharges (ID). Using microelectrodes in the hippocampal formations of 8 patients with drug-resistant temporal lobe epilepsy, we studied ID by simultaneously analyzing action potentials from individual neurons and the local field potentials generated by the surrounding neuronal network. We found that ~ 30% of the units increased their firing rate during ID and 40% showed a decrease during the post-ID period. Surprisingly, 25% of units showed either an increase or decrease in firing rates several hundred of milliseconds before the ID. In 4 patients, this pre-ID neuronal firing was correlated with field high-frequency oscillations at 40-120 Hz. Finally, we observed that only a very small subset of cells showed significant coincident firing before or during ID. Taken together, we suggested that, in contrast to traditional views, ID are generated by a sparse neuronal network and followed a heterogeneous synchronization process initiated over several hundreds of milliseconds before the paroxysmal discharges.